Wave simulation for the design of an innovative quay wall: the case of Vlorë Harbour - A. Antonini; R. Archetti; A. Lamberti (Natural Hazards and Earth System Sciences, 2017)
Sea states and environmental conditions are basic data for the design of marine structures. Hindcasted wave data have been applied here with the aim of identifying the proper design conditions for an innovative quay wall concept. In this paper, the results of a computational fluid dynamics model are used to optimise the new absorbing quay wall of Vlorë Harbour (Republic of Albania) and define the design loads under extreme wave conditions. The design wave states at the harbour entrance have been estimated analysing 31 years of hindcasted wave data simulated through the application of WaveWatch III. Due to the particular geography and topography of the Bay of Vlorë, wave conditions generated from the north-west are transferred to the harbour entrance with the application of a 2-D spectral wave module, whereas southern wave states, which are also the most critical for the port structures, are defined by means of a wave generation model, according to the available wind measurements. Finally, the identified extreme events have been used, through the NewWave approach, as boundary conditions for the numerical analysis of the interaction between the quay wall and the extreme events. The results show that the proposed method, based on numerical modelling at different scales from macro to meso and to micro, allows for the identification of the best site-specific solutions, also for a location devoid of any wave measurement. In this light, the objectives of the paper are two-fold. First, they show the application of sea condition estimations through the use of wave hindcasted data in order to properly define the design wave conditions for a new harbour structure. Second, they present a new approach for investigating an innovative absorbing quay wall based on CFD modelling and the NewWave theory.